L’effet du sulfite de sodium sur la conservation de la crevette rose « Palaemon Serratus » pendant la congélation - Bahloul, Manel (My University, 2019)
As part of protecting consumers and the risk assessment of public health, we have set ourselves in order to monitor the microbiological quality and evolution of the microform in health impact, the time of harvest juice that arrival in the consumer. Organoleptic quality that determines the state of freshness and degree of alteration of the product is intended to keep the food in and saves However, the decrease in the degree of weathering and extend the shelf life due to the effect of sodium sulphite (E221) reducing microbial spoilage and enzyme in the shrimp.